The effect of dietary threonine on growing pig growth performance - K G Friesen; B T Richert; J L Laurin; T L Weeden; Jim L Nelssen; Robert D Goodband (Kansas Agricultural Experiment Station Research Reports, 1992)
Sixty pigs (initially 68.57 lb BW) were used in a 28-d growth trial to determine the effect of increased dietary threonine on growth performance for the grower pig. The basal diet was formulated with corn and peanut meal to contain 1.00% dietary lysine and .40% dietary threonine. Sucrose was replaced by synthetic threonine to give dietary threonine levels of .50, .60, .70, and .80%. Two pigs were housed per pen for a total of six pens per treatment (12 pigs per treatment). Pig weights and feeder weights were recorded weekly to determine ADG, ADFI, and feed efficiency. On d 14 and 28 of the eXPeriment, serum samples were collected to determine serum urea N concentrations. From d 0 to 14, ADG increased quadratically and feed efficiency improved linearly and quadratically as dietary threonine increased. Average daily feed intake was not affected by dietary treatment. From d 14 to 28, ADG, ADFI, and feed efficiency were not affected by increased dietary threonine. Cumulative (d 0 to 28) ADG and ADFI were not significantly influenced by dietary treatment. However, ADG improve by 17% when dietary threonine was increased from .40 to .50%. Feed efficiency improved linearly and quadratically when dietary threonine was increased and was optimized between .50 and .60% dietary threonine (approximately 10 to 12 g/d) from d 0 to 28. Serum urea N was decreased as dietary threonine increased. Pigs fed .60% dietary threonine had the lowest serum urea N concentrations compared to the other treatments. These data suggest that the grower pig requires dietary threonine at approximately .50 to .60% (10 to 11 g/d) to optimize growth performance.; Swine Day, Manhattan, KS, November 19, 1992
Keywords: Swine day; 1992; Kansas Agricultural Experiment Station contribution; no. 93-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 667; Swine; Threonine; Pig